Analisis Efektivitas Buku Ajar Tematik - Bradley Setiyadi; Fina Thania Renata (Jurnal Pendidikan dan Pembelajaran, 2022)
This study aims to describe the effectiveness of the thematic textbooks for the Kurikulum 2013 at the SD YKPP in Jambi City by knowing the obstacles in implementing the 2013 thematic textbooks at the SD YKPP. In this study the method used was a qualitative method with a case study approach. In collecting data, this research conducted in-depth interviews with the participants. Participants who were interviewed consisted of one principal and six teachers. The results showed that (1) The application of thematic textbooks at SD YKPP had been going well by adjusting the conditions of students and schools. (2) The obstacle faced in implementing the thematic textbooks for the Kurikulum 2013 at the SD YKPP is the adjustment of the differences in the learning abilities of each student. (3) Thematic textbooks are considered to have been effectively implemented in the SD YKPP, supported by some evidence that the facilities and infrastructure at the SDYKPP are adequate, there is an increase in overall student achievement every semester, and the achievement of the objectives of the Kurikulum 2013